Integrasi Paradigma Keadilan Restoratif Kuhp Nasional Dalam Formulasi Hukum Acara Penyelesaian Perselisihan Hubungan Industrial Yang Berkeadilan Substantif - Khoirul Rohman; Mega Dewi Ambarwati (CV. SINAR HOWUHOWU, 2026)
The transformation of Indonesia’s national legal system through the enactment of Law Number 1 of 2023 concerning the Criminal Code (KUHP) signifies a paradigm shift in law enforcement from a retributive orientation toward a restorative justice approach. This transformation not only affects the criminal justice system but also creates opportunities for reconstructing dispute resolution mechanisms in other areas of law, including industrial relations dispute settlement. This study aims to analyze the synchronization of restorative justice principles within the National Criminal Code and their effectiveness in restoring workers’ rights through the Industrial Relations Dispute Settlement (PPHI) mechanism, as well as to examine the urgency of expanding electronic evidence in the adjudication of labor disputes. The research employs a normative juridical method using statutory, conceptual, and comparative approaches. The findings indicate that the procedural law governing industrial relations disputes remains predominantly formalistic, often failing to achieve substantive justice for workers. The integration of restorative justice values, the utilization of judicial pardon mechanisms, and the strengthening of electronic evidentiary systems have the potential to enhance the effectiveness of workers’ rights protection. Furthermore, the regulation of corporate criminal liability for non-compliance with Industrial Relations Court decisions may serve as a more effective legal instrument in ensuring employers’ adherence to final and binding judicial decisions.